Flight - Taylor, Kim, 1933-; Lyon, Chris (London : Belitha Press, 1992)
An introduction to the science of flight, in nature and in human technology. Also includes instructions for simple flight experiments.
Includes index.
Keywords: Aeronautics -- Juvenile literature; Flight -- Experiments -- Juvenile literature; Birds -- Flight -- Juvenile literature; Aeronautics; Flight -- Experiments; Experiments